Bursts of Star Formation and Radiation-driven Outflows Produce Efficient LyC Leakage from Dense Compact Star Clusters - Shyam H. Menon; Blakesley Burkhart; Rachel S. Somerville; Todd A. Thompson; Amiel Sternberg (The Astrophysical Journal)
The escape of LyC photons emitted by massive stars from the dense interstellar medium (ISM) of galaxies is a key bottleneck for cosmological reionization. The escape fraction varies significantly across and within galaxies, motivating further study of the underlying physical factors responsible for these trends. We perform radiation hydrodynamic simulations of idealized clouds with different gas surface densities (compactness) Σ ∼ 10 ^2 –10 ^5 M _⊙ pc ^−2 , meant to emulate star cluster-forming clumps ranging from conditions typical of the local Universe to the high ISM-pressure conditions encountered at high redshift. We find that dense compact star clusters with Σ ≳ 10 ^4 M _⊙ pc ^−2 efficiently leak LyC photons, with cloud-scale luminosity-weighted average escape fractions ≳80% as opposed to ≲10% for Σ ∼ 100 M _⊙ pc ^−2 . This occurs due to higher star formation efficiencies and shorter dynamical timescales at higher Σ; the former results in higher intrinsic LyC emission, and the latter implies rapid evolution, with a burst of star formation followed by rapid gas dispersal, permitting high LyC escape well before the intrinsic LyC emission of stellar populations drop (∼4 Myr). LyC escape in dense clouds is primarily facilitated by highly ionized outflows driven by radiation pressure on dust with velocities ∼3 times the cloud escape velocity. We also vary the (assumed) dust abundances ( Z _d ) and find a mild increase (∼10%) in the escape fraction for ∼100 lower Z _d . Our results suggest a scenario in which localized compact bursts of star formation in galaxies are disproportionately productive sites of LyC leakage. We briefly discuss possible observational evidence for our predictions and implications for cosmic reionization.